Human dehydrogenase/reductase (SDR family) member 8 (DHRS8): a description and evaluation of its biochemical properties - Lundová, Tereza; Štambergová, Hana; Zemanová, Lucie; Svobodová, Markéta; Havránková, Jana; Šafr, Miroslav; Wsól, Vladimír (Molecular and cellular biochemistry, 2016)
Dehydrogenase/reductase (SDR family) member 8 (DHRS8, SDR16C2) belongs to the short-chain dehydrogenase/reductase (SDR) superfamily, one of the largest enzyme groups. In addition to the well-known members which participate in the metabolism of important eobiotics and xenobiotics, this superfamily contains many poorly characterized proteins. DHRS8 is a member of the Multisubstrate NADP(H)-dependent SDR16C family, which generally contains insufficiently described enzymes. Despite the limited knowledge about DHRS8, preliminary indicators have emerged regarding its significant function in the modulation of steroidal activity, at least in the case of 3α-adiol, lipid metabolism and detoxification. The aim of this study was to describe additional biochemical properties of DHRS8 and to unify knowledge about this enzyme. The DHRS8 was prepared in recombinant form and its membrane topology in the endoplasmic reticulum as an integral protein with cytosolic orientation was demonstrated. The enzyme participates in the NAD(+)-dependent oxidation of steroid hormones as β-estradiol and testosterone in vitro; apparent K m and V max values were 39.86 µM and 0.80 nmol × mg(-1) × min(-1) for β-estradiol and 1207.29 µM and 3.45 nmol × mg(-1) × min(-1) for testosterone. Moreover, synthetic steroids (methyltestosterone and nandrolone) used as anabolics as well as all-trans-retinol were for the first time identified as substrates of DHRS8. This knowledge of its in vitro activity together with a newly described expression pattern at the protein level in tissues involved in steroidogenesis (adrenal gland and testis) and detoxification (liver, lung, kidney and small intestine) could suggest a potential role of DHRS8 in vivo.
Keywords: Middle Aged; Membrane topology; Expression; katalýza; mužské pohlaví; Catalysis; SDR16C2; Humans; Enzyme activity; DHRS8; Oxidoreductases; 17β-HSD11; lidé středního věku; lidé; Male; oxidoreduktasy